TOTAL PHENOLIC CONTENT AND FLAVONE BIOACTIVITY OF PEANUT HULLS AS ANTIOXIDANT AND ANTIPROLIFERATION TOWARD HELA CANCER CELLS - Alawiyah, Aika Latifah; Achmadi, Suminar Setiati; Syahbirin, Gustini (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to determine the total phenolic content, correlation of it with antioxidant capacity, and peanut hulls as an antiproliferation on Henrietta Lacks (HeLa) cancer cells, which Indonesia has a serious problem in term of cervix cancer. Methods: Peanut hulls were extracted by Soxhlet extraction, ultrasound vibration, and reflux boiling to obtain the best extraction method. The total phenolic content of the ethanol extract and the ethyl acetate fraction was determined using Folinâ€“Ciocalteu method. The 2,2-diphenyl-1-picrylhydrazylÂ (DPPH) assay was used to evaluated an antioxidant capacity of both samples. Identification of the isolated flavone was done by ultraviolet spectra andÂ analyzed using liquid chromatography-mass spectrometer. Inhibition of proliferation of HeLa cancer cells was tested for the purified fraction usingÂ 3-(4,5-dimethyl thiazole-2-yl)-2, 5-diphenyltetrazolium bromide assay. Results: The results of total phenolic content determination giving 262 (ethanol extract) and 532 (ethyl acetate fraction) mg gallic acid equivalent/gÂ extract, respectively. DPPH assay resulted antioxidant capacity with value of inhibitory concentration 50% (IC) was 36.36 (ethanol extract) andÂ 18.68 (ethyl acetate fraction) Âµg/mL, respectively. Identification of isolated flavone resulted an apigenin and indicated moderate potency in inhibitingÂ the proliferation of HeLa cancer cells with ICÂ 50Â value of 34 Âµg/mL.Â 50 Conclusions: There was a correlation between the total phenolics with antioxidant capacity of the peanut hulls. The isolated flavone is predominatedÂ by apigenin. This isolated compound is potential as antioxidant and inhibiting the proliferation of HeLa cancer cells moderately. Keywords: Peanut hulls, Total phenolic, Antioxidant capacity, Flavone, Apigenin, Henrietta Lacks cancer cells.